Preparation for International Assessment Research by Forming Types of Functional Literacy in Future Chemistry Teachers - Shernazarov Iskandar Ergashovich; Tilyabov Maksudjon Umurzokovich (Web of Journals Publishing, 2023)
The article presents the literacies and competencies needed to prepare future chemistry teachers for international assessment research. At the same time, concepts about functional literacy and its composition of competencies are given.
Keywords: functional literacy, communicative, literacy in emergency situations, activity literacy, knowledge of foreign languages, literacy in solving household problems, financial, natural-scientific, mathematical, reading literacy.